Sources and use of funds in Islamic banks - fichouche, hamza (Journal of Research in Finance and Accounting, 2020)
Islamic banks do not differ from conventional banks in terms of the financial sources that make up them, because all banks are financial institutions whose primary mission is to collect deposits and attract savings, but the qualitative difference between Islamic banking and traditional banking is the method of investing deposit and savings funds, which leads to a difference Intrinsic to the structure of accounts and budgets in the Islamic bank and other banks, as well as in the distribution of profits and returns for these investments, and the sources of funds in Islamic banks consist of internal - self - sources, and external sources, and the funds of Islamic banks are used The financing and banking services and social services